Effect of direct distributed load on the normative behavior to the stability of the light locally produced sandwich panels with two steel faces and a core of polyurethane (PUR) - صقور, أكرم; عمران, جلال (Latakia University Journal -Engineering Sciences Series, 2020)
Light sandwich panels are increasingly employed in engineering facilities because of their high acoustic and thermal insulation, in addition to adapting its construction investment as elements of fast construction according to the materials used and production technology to work as walls and plates carrier internal and external, where they are able to receive the loading systems to which the facility is subjected of normal service loads, wind and snow and transport them via secondary beams to the other major carriers in the required facility. We do not have yet official scientific references that adopt certain equipment by the mechanism of testing the core material of these panels in the first place, and include their physical and mechanical properties within a specific structural calculation system to adjust the structural design criteria by defining its modulus of elasticity on tension, compression, shear and adhesion related primarily to the quality and specifications of the product, either direct or long term load to determine the maximum designed load of these panels. This paper seeks to introduce a system to test the effect of distributed direct static load substituted on the sandwich panel and its behavioral mechanism, to infer the empirical derivation for the relationship of the designed normative behavior of the tested product as load-transition, or rather a stress-transition, by using an experimental apparatus specifically designed to test such material of locally produced sandwich panels with core of polyurethane, and generalization of its findings to form a basic database to analyze and design the components of the panel.